IMPLEMENTASI PSAK 112 TENTANG AKUNTANSI WAKAF PADA LEMBAGA YAYASAN WAKAF HAROEN ALY BANDA ACEH - Nurliza, Dinda; Fitri, Meutia (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2023)
The study objective is to assess the implementation of PSAK 112 for waqf accounting, covering recognition, measurement, presentation, and disclosure, at the Haroen Aly Banda Aceh Foundation. The method used is a qualitative method with a descriptive approach. This research uses primary data obtained from interviews. Data is processed by editing, organizing, and analyzing. The results of this study indicate that the Haroen Aly Wakaf Foundation has not fully implemented PSAK 112 regarding waqf accounting, several transaction characteristics in PSAK 112 have not been used and financial reports have not been fully prepared according to reporting standards as a nazir who manages waqf funds.